DIVERSITY AND DISTRIBUTION OF ERICACEAE SPECIES IN MUONG LA NATURE RESERVE, SON LA PROVINCE - Thanh Trang, Pham; Thi Thu, Nguyen; Thi Tuyen, Phung; Van Truong, Do; Ta Chun, Ly; Manh Quyen, Hoang (Journal of Forestry Science and Technology, 2018)
This study provides diversity of species composition, phenology and distribution of the family Ericaceae in Muong La Nature Reserve (Muong La NR), Son La province. A total of 11 species belong to six genera consisting of Rhododendron, Craibiodendron, Vaccinium, Lyonia, Monotropastrum, and Enkianthus were recorded for the flora of Muong La NR. Most of Ericaceae species distribute in a mountain of ever green subtropical forest from 1,500 to more than 2,400 m above sea level where covered by foggy condition year-round. The flowering or fruiting periods of nine Ericaceae species were also observed in this study. The results indicated that three species have the flowering time from June to July (Rhododendron maddenii sub sp. crissum (Franch.) Cullen, Lyonia villosa var. villosa Ridley, and Rhododendron arborium subsp. cinnamomum (Lindl) Tagg) and six species had fruiting time from July to August (Rhododendron tanastylum var. tanastylum Ridley, Rhododendron nuttalii Booth, Craibiodendron henryi W. W. Sm., Vaccinium dunalianum Wight, Enkianthus quinqueflorus var. serrulatus Wilson, and Monotropastrum humile (D. Don) Hata.) The important information of species diversity, distribution and phenological characteristics of Ericaceae family in Muong La NR in this study will be a useful reference for further work.